Dinasti Politik Dalam Pemerintahan Lokal Di Kota Bontang, Kalimantan Timur - Purwanti, Uci Dewi; Alfirdaus, Laila Kholid (Journal of Politic and Government Studies, 2020)
Politics of Bontang City discusses the model and achievements of family politics in leading Bontang City. The method used in this research is a qualitative approach with descriptive methods for the phenomena that occur, the emphasis of this research is interpretive. The results of this study found that the political family of Andi Sofyan Hasdam and Neni Moerniaeni and their son Andi Faisal Sofyan Hasdam have become political families in Bontang City. Meanwhile, the political dynasty model owned by the city of Bontang is the arisan model and the cross-space model, where the arisan model is realized by providing power regeneration to the political family, while the cross-spatial model is realized by the family. distribution of control by husbands and wives as well as mothers and children in power. executive and legislative in the city of bontang. Research has some opinions that there is a bloodline of the government family. At first glance there is nothing wrong with dynastic politics. Especially when referring to the democratic proposition that every citizen has the same right to be elected and to vote. However, it cannot be denied that the political dynasties that have developed so far have damaged the essence of democracy itself.